The Changing of Political Orientation of Masyumi Party During 1950-1959 - Alfi Hafidh Ishaqro; Alamsyah Alamsyah; Dewi Yuliati (Diponegoro University, 2017)
Through historical method, this article studies the Shifts in Political Ideological Orientation of Masyumi Party during the Liberal Democracy Era 1950–1959. The shifted orientations of Masyumi Party included a shif of orientation in its principle, form of government and the government executive system.The establishment of Masyumi Party was the apex of the Japanese concern in trying to map the axis of the powers of various groups in Indonesia. The formations of PUTERA, which bore the nationalist inclination and MIAI, which tended to accommodate urban Muslims were not attractive enough to win the hearts and empathy from the Indonesian native communities for its occupation in Indonesia. Masyumi Party made Islam as a its struggling principle, not only as a symbol but also tha ideology and spirits in conducting the various siyasah preaches within the scope of political struggles. Numerous internal dynamics were then occuring in the body Masymi Party. The Party’s change in its orientation began to be visible, indicated by the idea suggested by M. Natsir to formulate the Constitution or Law of General Election.The formation of the General Election Law made M. Natsir and Masyumi the symbol of the establishment and growth of democracy in the Republic of Indonesia, which became more evident when M. Natsir was ousted and the subsequent working cabinet heads failed to hold a General Election. And finally, at the end of 1955 under the leadership of Burhanuddin Harahap, who was himself a Masyumi figure, a general election was held for the first time. The political attitude shown by Masyumi indicated that Masumi Party had shifted its political orientation. Masyumi Party, which originally struggled to implement Islam by employing the Syura in forming a government was helplessly compromising its principle by following and combining itself into a democracy model the initiator of which was the leader of Masyumi Party itself. Such political behavioral changes were associated with the reasoning of the then leaders of Masyumi Party, who tended to accommodative and excessively compromising.